Neuroecotoxicology: Effects of environmental heavy metal exposure on the brain of African giant rats and the contribution of vanadium to the neuropathology - Ifukibot Levi Usende; James Olukayode Olopade; Idris Ayodeji Azeez; Anna Andrioli; Molakun O. Bankole; Funmilayo E. Olopade; Allam A. Nafady; Marina Bentivoglio (IBRO Neuroscience Reports, 2022)
Increased exploitation of minerals has led to pollution of confined environments as documented in Nigeria Niger Delta. Information on the effects on brain of such exposure is limited. Due to its exploratory activities, the African giant rat (Cricetomys gambianus) (AGR) provides a unique model for neuroecotoxicological research to determine levels of animal and human exposure to different pollutants. This study aims to unravel neuropathological features of AGR sampled from three agro-ecological zones of Nigeria. Fifteen AGR were sampled according to previously determined data on heavy metal exposure: high vanadium, high lead, and low metals. Eighteen AGR were collected from low metal zone and divided into two groups. Control group received vehicle while SMV exposed group received 3 mg/kg sodium metavanadate (SMV) intraperitoneally for 14days. Brain immunohistochemical analyses were conducted, and ultrastructural changes were studied in experimentally exposed group. Results showed significant loss of tyrosin hydroxylase, parvalbumin, orexin-A and melanin concentration hormone containing neuronal populations in brains obtained from high vanadium and high lead zones and in experimentally intoxicated SMV groups. Similarly, significant decrease numbers of dendritic arborations; extracellular matrix density, perineuronal nets; astrocytes and microglia activations are documented in same groups. Ultrastructural studies revealed mass denudation, cilia loss, disintegration of ependymal layer and intense destructions of myelin sheaths in SMV exposed group. These are the first “neuroecotoxicological” findings in distinct neuronal cells. The implications of these findings are highly relevant for human population living in these areas, not only in Nigeria but also in similarly polluted areas elsewhere in the world.